Iraq’s regional strategic performance under the Iranian-Saudi agreement - Qasim Alwan saeed; Muhammad Ali Hammoud; Muammar Khaled Abdel Hamid (Tikrit Journal For Political Science, 2023)
Iraq has sought to play a role in mediating the Saudi-Iranian talks for several rounds, and Iraqi Prime Minister Muhammad Shia al-Sudani received a phone call from the Secretary of the Iranian Supreme National Security Council (Ali Shamkhani), through which he expressed his “thanks to Iraq for its role in the negotiations between the Kingdom of Saudi Arabia and Saudi Arabia and the Islamic Republic of Iran, and the Iraqi efforts made to bring views closer between the two countries, which contributed to reaching a new agreement between them in Beijing.